OPEN-KTH-3dMODELS: An Open Dataset of Building Models at KTH Campus Valhallavägen - Mohan, Naveen; Sainte Catherine, Maxime; Jose, Lester (Royal Institute of Technology, 2023)
OPEN-KTH-3dMODELS: An open dataset of building models at KTH Campus Valhallavägen

Open-KTH-3dModels is a subproject of the AD-EYE testbed for Automated Driving and Intelligent Transportation Systems.

The dataset comprises of a series .blend files that have prominent buildings from KTH campus Valhallavägen.

The dataset also contains PreScan compatible models that can be used wtih AD-EYE (https://www.adeye.se/)

Visualisation video: https://www.youtube.com/watch?v=F6NfCiul3oELearn more at https://www.adeye.se/open-kth-3dmodels or contact adeye@md.kth.se

The AD-EYE testbed is based on the design presented in the work "AD-EYE: A Co-Simulation Platform for Early Verification of Functional Safety Concepts"

Original paper: https://doi.org/10.4271/2019-01-0126

Preprint available at: https://arxiv.org/abs/1912.00448

Citation:

Naveen Mohan, Martin Törngren, "AD-EYE: A Co-Simulation Platform for Early Verification of Functional Safety Concepts", SAE Technical Paper 19AE-0203/2019-01-0126, https://doi.org/10.4271/2019-01-0126

Notes:

Modelling work primarily performed by Lester Jose, during his internship with AD-EYE.
Keywords: Electrical Engineering, Electronic Engineering, Information Engineering; Elektroteknik och elektronik